Pemanfaatan LNG sebagai sumber energi di Indonesia - Nurhadi Budi Santoso (Jurnal Rekayasa Proses, 2014)
The need of energy supplies in Indonesia, especially on diesel demand is increasing every year. However, this increase could not be fulfilled by national oil based energy supply due to the decrease of oil production and there has not been significant increase in term of oil fractionation plants. As a consequence, diesel import could not be avoided resulting an additional burden in nation budgeting. In order to solve this problem, LNG might be an alternative. Thus, diesel import can be eliminated; furthermore, domestic industries can be more competitive. Although Indonesia is one of the major LNG producers, most of the LNG production is exported to Japan, Korea, and China, but LNG has not been utilized by the society as well as domestic industries. A massive socialization of the utilization of LNG to replace diesel energy should be conducted. Moreover, facilities and infrastructures including transportation, storages, and converter kits have to be built to support this conversion process. Based on the cost saving analysis, the use of dual fuel (diesel and LNG) in a machine could possibly save 20-25% in comparison to that machine using single fuel (diesel).